PENERAPAN MODEL BLENDED LEARNING BERBANTUAN WHATSAPP UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA - Asa’aro Herman Hulu (UNIB Press, 2022)
This study aims to describe the application of the Whatsapp-assisted Blended Learning model to increase student activeness and learning achievement in social studies of the eighthgrade students of SMP Negeri 10 Pagar Alam. The research design used was classroom action research and quasi-experimental. The research subjects were grade VIII.B students of SMP Negeri 10 Pagar Alam even semester of the 2020/2021 school year. The quasi-experimental sample was class VIII.A and class VIII.c at SMP Negeri 10 Pagar Alam. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean (mean), percentage, and t-test. The results showed that the application of the Whatsapp-assisted Blended Learning model could increase the activeness and learning achievement of the eighth garde students of SMP Negeri 10 Pagar Alam